Impact of Rare Earth Element (REE) Additions on Electrode Performance in Electrooxidation Systems for Industrial Wastewater Treatment - Öztürk, Dilara; Güzel, Beyzanur; Demiray, Halil Berk; Demirci, Gamze; Kara, Serdar; Akyol, Abdurrahman (Avestia Publishing, 2025)
Pharmaceutical wastewater is among the wastewaters that are difficult to treat and monitor due to the different pharmaceutical ingredients they contain. In particular, as a result of the untreated release of different pharmaceutical ingredients into the receiving environment, it is inevitable that natural life will be affected, and mutations can occur. It has been reported in the literature that conventional methods are weak in the treatment of pharmaceutical industry wastewaters and that advanced oxidation methods can be efficient[1], [2]. In particular, the electrooxidation method has come to the forefront because it is an effective and green technology that targets mineralization[3]. In the electrooxidation method, the efficiency changes with the effect of the electrode material and with two types of oxidation mechanisms: direct and indirect[4], [5]. The composition of the electrodes is very important for this method[6]. In this study, the effect of the electrode material on the system was investigated. In this context, mixed-metal oxide electrodes were produced using the thermal decomposition method[7]. The selected metal coating was determined to be the result of the Ti/IrO2-RuO2-SnO2 composition, which is also frequently used in the literature, being doped with REEs. La and Ce were used as REEs. The ratios in the coating were selected as Ir:Ru:Sn:REE molar as 40:59:20:1. Comparison experiments were conducted with synthetic and industrial wastewater containing paracetamol(PCT) from the pharmaceutical industry located in Gebze. In synthetic 50 ppm PCT solution, at a current density of 350 A/m2, pH 5 and conductivity was 3.5 mS/cm, removal efficiencies were obtained as 39.8% TOC and 92% PCT removal for Ti/IrO2-RuO2-SnO2 composition. In the composition containing La, 53.1% TOC removal and 98% PCT removal were obtained. In the composition containing Ce, 47.8% TOC removal and 95% PCT removal were obtained. Wastewater characterization was performed on the composite samples before starting the study, and it was observed that the PST content was 250 ppm. In the study, while 94% PCT removal was achieved in 180 min at a current density of 350 A/m2 with the La dopped electrode and 90% PST in the Ce dopped electrode. According to the TOC results, the results were %10.5 for La dopped electrode and %6.5 for Ce dopped electrode. When the electrodes were compared according to HPLC measurements, it was observed that the most successful electrode was La dopped electrode, and the addition of NTE yielded successful results. While TOC removals remained low due to the mixed and complicated structure of the wastewater, PCT removals were quite successful for a high concentration wastewater. This was achieved by enhancing the electrocatalytic properties of the electrodes. Thus, it can be said that the addition of NTE yielded successful results. In addition, by improving these compositions of electrodes, a hybrid system can be used and much more successful removal efficiencies can be achieved. © 2025 Elsevier B.V., All rights reserved.
10th World Congress on Civil, Structural, and Environmental Engineering, CSEE 2025 -- Barcelona -- 330019